Mer de Kara, côte nord de Sibérie, Enisej (Iénisseï) / d'après les documents les plus récents , Service hydrographique de la marine . 1927 (1945)
Corr. . 1945 Depths shown by bathymetric isolines and soundings.; Map in 4 segments.; Selected lights shown in orange Color; 1:250,000